About wine - Henderson, Patrick (Thomson Delmar learning, 2007)
About Wine is a unique resource designed for those who require practical information on how to manage wine and wine sales for restaurants and the hospitality business. Unlike other texts on this subject, this text seeks first to give the reader background information on the origins of wine and how it is produced, and then builds upon this knowledge with information on the wine producing regions of the United States and the World. The numerous variations of wine produced in Europe, North America, and the Southern Hemisphere are presented. Special features of the text include detailed color diagrams and photographs, and useful appendices designed for use as a quick reference or a starting place for more research on topics of interest